Design and Development Based Learning Media Application Using Mobile App Inventor - Rini Sefriani; Popi Radyuli; Nurhidayati Nurhidayati; Rina Sepriana (International Journal of Educational Development and Innovation, 2021)
This research and development aims to produce a product in the form of mobile application-based learning media for class X Vocational High School students. This type of research is research and development using a 4-D development model. The instrument used in this study was in the form of a questionnaire distributed to teachers and students as well as experts to test the validator. Based on the analysis, it was obtained that the validator test for this mobile application-based learning media was 90.33%, with a very valid interpretation of the validity level of use. The results of the overall practicality assessment from the practicality test were assessed at 86.77%, so that the level of practicality can be interpreted as very practical to use. The results of the overall assessment of the effectiveness test for the assessment of the effectiveness of 87.29% Reviews its effectiveness so that it can be interpreted very Effectively used. Thus, this learning media is very valid to be used, very practical to use and very effectively used in learning in vocational high schools